CHARACTERISTICS OF RECEIVING WATERS IN A SHRIMP AQUACULTURE AREA IN CAI NUOC, CA MAU - Tho, Nguyen; Anh, Nguyen Thi (Vietnam Journal of Earth Sciences, 2012)
Unregulated shrimp aquaculture development has posed several negative impacts to the receiving waters of the coastal Cai Nuoc district, Mekong delta of Vietnam where most of the land area was converted to shrimp farms since 2000. Enhanced organic loadings and salinisation of surface water and sediment are the major physico-chemical impacts. Increasing levels of organic loadings and suspended solids were found in the receiving waters, mainly as a result of shrimp farm discharge and run-off. The salinization has been caused by the irrigation of saltwater to the interior fields for shrimp culture. The shrimp aquaculture practice has also caused a reduction in phytoplankton diversity and changes in the structures of zooplankton and zoobenthos community. The bacterial community in the receiving waters has also been enriched as a result of enhanced organic loadings. Shrimp aquaculture practices might deteriorate the quality of the receiving waters, which is used as input water for shrimp farms.